Clinical Practice Guidelines for Cerebral Abscess Treatment - Danny Barrueta Reyes; Néstor Pulido Ríos (Medisur)
Clinical Practice Guidelines for Cerebral Abscess Treatment. It has been defined as a festering process caused by any germ and placed inside the cerebral parenchyma; this is a diagnostic and therapeutic challenge for surgeons and general doctors since the clinical and radiological manifestations are often imprecise. This document describes its etiological agents, clinical presentation, diagnosis and treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.